Discovering the Potent Inhibitors Against Babesia bovis in vitro and Babesia microti in vivo by Repurposing the Natural Product Compounds - Li, Yongchang; Rizk, Mohamed Abdo; Galon, Eloiza May; Liu, Mingming; Li, Jixu; Ringo, Aaron Edmond; Ji, Shengwei; Zafar, Iqra; Tumwebaze, Maria Agnes; Benedicto, Byamukama; Yokoyama, Naoaki; Igarashi, Ikuo; et al. (Frontiers in Veterinary Science, 2021)
In the present study, we screened 502 natural product compounds against the in vitro growth of Babesia (B.) bovis. Then, the novel and potent identified compounds were further evaluated for their in vitro efficacies using viability, and cytotoxicity assays. The in vivo inhibitory effects of the selected compounds were evaluated using B. microti “rodent strain” in mice model. Three potent compounds, namely Rottlerin (RL), Narasin (NR), Lasalocid acid (LA) exhibited the lowest IC50 (half-maximal inhibitory concentration) as follows; 5.45 ± 1.20 μM for RL, 1.86 ± 0.66 μM for NR, and 3.56 ± 1.41 μM for LA. The viability result revealed the ability of RL, and LA to prevent the regrowth of treated parasite at 4 ×, and 2 × IC50s, respectively. While, 4 × IC50 of NR- was sufficient to stop the regrowth of parasite. The hematology parameters of B. microti in vivo were different in the NR-treated groups as compared to the infected/untreated group. Interestingly, intraperitoneal administration of NR exhibited inhibition in the growth of B. microti in mice similar to those observed after administration of the commonly used antibabesial drug, diminazene aceturate (DA) (76.57% for DA, 74.73% for NR). Our findings indicate the richness of natural product compounds by novel potent antibabesial candidates and the identified potent compounds especially NR might be used for the treatment of animal babesiosis.